The influence of postoperative environment on patient pain and satisfaction: a randomized trial - Hill, Austin M.; Crisp, Catrina C.; Shatkin-Margolis, Abigail; Tam, Tiffanie; Yook, Eunsun; Kleeman, Steven; Pauls, Rachel N. (American journal of obstetrics and gynecology, 2020)
Improving the patient experience, controlling pain with nonopiate therapies, and preparing for value-based reimbursement are increasingly important foci for both physicians and hospitals. We aimed to determine whether the addition of music and a natural landscape image to postoperative hospital rooms would result in improved pain and satisfaction scores among inpatients undergoing pelvic reconstructive surgery. This randomized controlled trial was approved by an Institutional Review Board. Eligible candidates were 18–85 years old, English speaking, and scheduled to undergo native tissue vaginal vault suspension for symptomatic pelvic organ prolapse. Patients with history of a chronic pain or substance abuse were excluded. Subjects were advised that the purpose of the study was to assess the effect of changes to the hospital environment on patient experience but were blinded to their group and intervention details. Changes included a landscape image mounted to the wall and access to a speaker with preprogrammed music selections. The intervention group was instructed to listen to their preferred music for a minimum of 2 30-minute sessions postoperatively. The control group had a standard hospital room, without music or landscape. All patient rooms were private. The primary outcome was the visual analog scale for pain in the morning of postoperative day 1. Secondary outcomes included narcotic use, likelihood to refer family to the same hospital facility, satisfaction with care and the hospital, and perception of a healing environment. A sample size of 43 subjects per arm was calculated to detect a difference of 10 mm in visual analog scale pain score. A total of 133 subjects were enrolled; primary outcome data were available for 92 (46 per arm). The mean age was 63.8 (standard deviation, 9.5) years, median Charlson comorbidity score was 2 (min, 0; max, 7), and 94.6% of subjects were white. On postoperative day 1, median visual analog scale pain scores were low (28.8 mm [0, 86]; 24.5 mm [0, 81]) and did not differ between intervention and control, respectively (P=.57). Total morphine equivalents (P=.817) and nursing pain scores (P=.774) were also similar. However, the intervention group displayed a higher likelihood to refer family members to the hospital (98 mm (47, 100); 96 mm (65, 100); P=.037). At postoperative 2 weeks, the intervention group indicated higher satisfaction with their care (98 mm, (34, 100); 95 mm (42, 100); P=.032), the hospital (98 mm (71, 100); 94 mm (6, 100); P=.004), and the healing environment provided during their stay (98 mm; 92 mm (19, 100); P=.020) than those in the standard hospital rooms. In this randomized trial, we found music and landscape imagery did not substantially affect postoperative pain scores; however, they had a positive effect on the postoperative experience. Furthermore, this effect appeared to broaden 2 weeks after surgery. Given the importance of value-based care, interventions such as these should be emphasized to enhance patient satisfaction, quality scores, and overall well-being.